2012
DOI: 10.1093/ehjci/jes238
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of left ventricular myocardial strain in obese children

Abstract: Childhood obesity may be associated with an early alteration of the longitudinal and circumferential LV strain. These findings have potentially significant clinical implications for the outcomes and follow-up of obese children meriting further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
5
36
1
Order By: Relevance
“…These results confirm previous reports that obese adolescents and adults, with normal function by conventional measures have decreased GLS and early diastolic GLSR in association with the severity of obesity. 7, 31 These results raise the question of whether ventricular dysfunction may precede the development of ventricular structural abnormalities in some of obese adolescents. The development of ventricular dysfunction may serve as an early marker of cardiovascular involvement before the manifestation of cardiac clinical and structural signs of the impact of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results confirm previous reports that obese adolescents and adults, with normal function by conventional measures have decreased GLS and early diastolic GLSR in association with the severity of obesity. 7, 31 These results raise the question of whether ventricular dysfunction may precede the development of ventricular structural abnormalities in some of obese adolescents. The development of ventricular dysfunction may serve as an early marker of cardiovascular involvement before the manifestation of cardiac clinical and structural signs of the impact of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study assessed cardiac function in obese children using 2DSTE and showed that LV GLS negatively correlated with HOMA-IR and BMI Z-score 35 . However, the multivariate analysis performed in this study did not include measures of IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50-62,64-69 There were eight manuscripts eligible from Friedberg and Mertens et al (Toronto) 20,50-56 and six manuscripts eligible from Marcus et al (Netherlands) 16,58-62 that compared strain from a large database of overlapping pediatric controls to different disease outcomes in children, or healthy children. In consultation with the authors, the datasets from Fernandes et al 20 (Toronto) and Marcus et al 16 (Netherlands) were chosen as they contained the largest amount of control patients.…”
Section: Electronic Database Search Hedgesmentioning
confidence: 99%
“…Exclusion criteria included valvular disease, dilated or hypertrophic or myocardiopathy were excluded. Clinical characteristics as age, gender, height, weight and risk factors as hypertension (defined as systolic blood pressure ≥ 140 mmHG and diastolic pressure ≥ 90mmHg [18]), dyslipidemia (cholesterol levels above>200 mg/dl and c-ldl > 160 mg/dl [19], diabetes (A1C ≥ 6.5% or fasting plasma glucose ≥ 126 mg/dL [20]) and smoking were asked before the assessment as part of their clinical history.…”
Section: Introductionmentioning
confidence: 99%